Yüksek fruktoz tüketiminin dişi Sprague Dawley ratlarda metabolik parametreler ve karaciğer histolojisi üzerine etkileri - Kaya, Can Ayhan; Özercan, İbrahim Hanifi (MediHealth Academy Yayıncılık, 2026)
Giriş/Amaç: Bu çalışmada, uzun süreli yüksek fruktoz tüketiminin dişi Sprague Dawley ratlarda metabolik parametreler ve karaciğer histolojisi üzerindeki etkileri araştırılmıştır. Materyal ve Metot: Deney grubuna 90 gün boyunca %20 fruktoz takviyeli su verilirken, kontrol grubu standart diyetle beslenmiştir. Bulgular/Sonuçlar: Sonuçlara göre, fruktoz grubunda yem tüketimi (356.47 ± 83.40 g vs. 1078.67 ± 79.97 g) ve protein alımı (81.28 ± 19.02 g vs. 245.94 ± 18.23 g) anlamlı derecede azalmış (p

Aims: This study investigated the effects of long-term high fructose consumption on metabolic parameters and liver histology in female Sprague Dawley rats. Methods: The experimental group received 20% fructose-supplemented water for 90 days, while the control group was fed a standard diet. Results: Results showed that the fructose group had significantly lower feed intake (356.47±83.40 g vs. 1078.67±79.97 g) and protein intake (81.28±19.02 g vs. 245.94±18.23 g; p
Effects of high fructose consumption on metabolic parameters and liver histology in female sprague dawley rats
Keywords: Nutritional Science; Beslenme Bilimi; Public Health Nutrition; Halk Sağlığı Beslenmesi; Clinical Nutrition; Klinik Beslenme